Spectroscopic studies of Er3+-Yb3+ codoped multicomposition tellurite oxide glass - Baki, S.O.; L.S., Tan; C.S., Kan; Kamari, H.M.; Noor, A.S.M.; Mahdi, M.A. (Universiti Kebangsaan Malaysia, 2014)
Multicomposition of Er3+-Yb3+ codoped tellurite oxide, TeO2-ZnO-PbO-TiO2-Na2O glass has been investigated. A detailed spectroscopic study of the Judd-Ofelt analysis has been performed from the measured absorption spectrum in order to obtain the intensity parameters Ωt (t=2, 4, 6). The calculated Ωt values were then utilized in the determination of transition probabilities, radiative lifetimes and branching ratios of the Er3+ transitions between the J(upper)-J’(lower) manifolds. Both visible upconversion and near-infrared spectra were characterized under the 980 nm laser diode excitation at room temperature.